2020
DOI: 10.1021/acs.jpcc.0c00632
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Oxygen Reduction Reaction Mechanism on the Neighboring Active Sites of a Boron-Doped Pyrolyzed Fe–N–C Catalyst

Abstract: We study the oxygen reduction reaction (ORR) mechanism on the neighboring active sites of a B-doped pyrolyzed Fe−N−C catalyst using a combination of density functional theorybased calculations and microkinetic simulations. The structure of the neighboring FeN 4 and B-doped active sites facilitates the O 2 side-on adsorption for a facile dissociation process. This situation gives the B-doped catalyst system a flexibility to access both associative and dissociative reduction mechanisms. Such a mechanism does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…One promising solution that has been successfully applied is co-doping boron and nitrogen into the TM-N-C . Our group previously reported that the existence of boron and nitrogen substitutional defect adjacent to an FeN 4 active site provides a controlled additional active site to facilitate a more preferred ORR dissociative mechanism that led to a significant improvement of its kinetics. , On the basis of this result, we thus anticipate that the same scenario can lower the overpotential of CO 2 RR and consequently enhance its rate.…”
Section: Introductionmentioning
confidence: 84%
“…One promising solution that has been successfully applied is co-doping boron and nitrogen into the TM-N-C . Our group previously reported that the existence of boron and nitrogen substitutional defect adjacent to an FeN 4 active site provides a controlled additional active site to facilitate a more preferred ORR dissociative mechanism that led to a significant improvement of its kinetics. , On the basis of this result, we thus anticipate that the same scenario can lower the overpotential of CO 2 RR and consequently enhance its rate.…”
Section: Introductionmentioning
confidence: 84%
“…Additionally, Zhao and Chen 21 found that the metallic atoms doped two‐dimensional boron nitride (2D‐BN) materials is a suitable candidate for ORR in replacing Pt‐based catalysts. Saputro et al 22 prepared the B‐doped FeNC catalyst pyrolyzed, exhibiting the better performance compare to the B un‐doped. Furthermore, they chose the most stable active site configuration, indicating that the active site could reduce the activation energy of oxygen dissociation with DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the microkinetic model derivation for typical hydrogenation reaction can be found in our recent works [13,[16][17][18].…”
Section: Dft Calculations and Microkinetic Modelingmentioning
confidence: 99%